Insights sobre a evolução termo-tectônica da Ilha Alexander, Península Antártica, via Termocronologia por Traços de Fissão e geocronologia U-Pb em zircão. - Nunes, Lucas Alexander (Universidade Federal de São Carlos, 2025)
The thermo-tectonic evolution of the western Antarctic Peninsula remains poorly understood. Although geochronological studies have already been conducted in the region using methods such as U-Pb, Lu-f, and others—capable of dating the origin and emplacement of plutonic, volcanic, or sedimentary rocks— here is still a significant lack of data in intermediate to low-temperature ranges. Such data are essential for identifying geological events that occurred after the crystallization of the rocks, including processes such as denudation, uplift, and exhumation. In this context, this study applied Fission Track Thermochronology (FTT) and U-Pb geochronology in zircon from samples collected on Alexander Island, Antarctic Peninsula, aiming to better understand its thermo-tectonic evolution. This methodology is well-suited to addressing significant uncertainties regarding the age of igneous and sedimentary components of the island. Zircon is a common accessory mineral in igneous, sedimentary, and metamorphic rocks. It is physically and chemically resistant, capable of "surviving" long geological periods and, in many cases, preserving a record of each geological event it has undergone. It incorporates trace elements such as U, Th, and Pb into its crystal structure, which is crucial for geochronological analyses, including the U-Pb method also applied in this study. Its ability to retain thermal history information from the source area is invaluable for elucidating geological processes related to a variety of geodynamic settings. Consequently, FTT in zircon has been widely used in association with other radiometric dating methods, such as those mentioned above. As a result, new insights were obtained on the region's geological evolution, contributing to the understanding of tectonic processes that occurred during the Mesozoic.
Insights into the thermo-tectonic evolution of Alexander Island, Antarctic Peninsula, via Fission Track Thermochronology and U-Pb zircon geochronology.
Keywords: Zircão; Termocronologia por Traços de Fissão; U-Pb; Península Antártica; Ilha Alexander; Zircon; Fission Track Thermochronology; Antarctic Peninsula; Alexander Island; CIENCIAS EXATAS E DA TERRA::GEOCIENCIAS; CIENCIAS EXATAS E DA TERRA::FISICA::FISICA NUCLEAR::DESINTEGRACAO NUCLEAR E RADIOATIVIDADE